A COMPARATIVE STUDY OF DIFFERENT METHODS FOR OBTAINING AN INDEX OF NITROGEN AVAILABILITY IN UPLAND SOILS (Biological Sciences - PJSIR, 2022)
A study on 50 soils with wide range of properties was conducted to find out a simple, rapid and reliable methodof obtaining an index or soil N availability. Three chemical methods; mineral plus mincralizablc N determination bymodified alkaline permanganate method, mineral N as (NH4 + NO)) and NOJ-N estimation by 2 NKCI were foundpromising as the soil N values obtained by these methods showed high correlation with mineral N of incubation test(r = 0.92, 0.88 and 0.85, respectively) and N uptake by wheat plants (r = 0.90, 0.87 and 0.85, respectively). Therelationship between yield response of wheat plants to applied N in pots and soil available N determined by the threemethods was also studied.